Biological activity and specificity of Miridae-induced plant volatiles - Pérez-Hedo, Mertixell; Rambla, Jose L.; Granell, Antonio; Urbaneja, Alberto (2019)
The ability of zoophytophagous predators to produce defensive plant responses due to their phytophagous behavior has been recently demonstrated. In the case of tomatoes, the mirids Nesidiocoris tenuis and Macrolophus pygmaeus are able to attract or repel pests and/or natural enemies in different ways. Nevertheless, the herbivore-induced plant volatiles (HIPVs) released by the phytophagy of both mirids, which are responsible for these behaviors, are unknown. In this work, the HIPVs produced by the plant feeding of N. tenuis and M. pygmaeus were characterized. In addition, the role of each HIPV in the repellence or attraction of two tomato pests, Bemisia tabaci and Tuta absoluta, and of the natural enemy Encarsia formosa was evaluated. Six green leaf volatiles (GLVs) plus methyl salicylate and octyl acetate clearly stood out as major differential peaks on the chromatogram in a directed analysis. The six GLV and methyl salicylate were repellent for B. tabaci and attractive to E. formosa, whereas they showed no effect on T. absoluta. Octyl acetate, which was significantly present only in the M. pygmaeus-punctured plants, was significantly attractive to T. absoluta, repellent to E. formosa and indifferent to B. tabaci. Unlike the remaining HIPVs, octyl acetate was emitted directly by M. pygmaeus and not by the plant. Our results showed that mirid herbivory could modulate the pest and natural plant enemy locations, since tomato plants release a blend of volatiles in response to this activity. These results could serve as a basis for future development of plant protection.